Using Social Media Marketing to Improve Marketing Performance: The Role of Digital Customer-Centric Intimacy Capability - Reza Rahmadi Hasibuan; Suliyanto Suliyanto; Weni Novandari (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study clarifies the gap in research on the impact of social media marketing on marketing performance in the hospitality industry. This study advances the understanding of effective digital marketing strategies for Micro, Small, and Medium Enterprises (MSMEs) in the aesthetic healthcare sector and offers practical recommendations for optimizing social media for better marketing results. Methodology: This study surveyed MSMEs in the aesthetic health services sector in Central Java. With a population of 288, a 5% margin of error required a minimum sample size of 155 respondents. Data were analyzed using the Validating a New Construct Test and Structural Equation Modeling (SEM). Results: This study explains the variations in previous research by identifying the mediating and moderating variables. Social media use, supported by digital customer-centric intimacy, improves the effectiveness of marketing. Conclusions: This study addresses the research gap by showing that differences in earlier findings can be explained by the mediating and moderating variables. These results offer a model that integrates previous research by including digital customer-centric intimacy capability as a mediating variable. Limitations: The rapidly changing digital landscape and evolving consumer behavior limit the generalizability of these findings to the present context. Future shifts in social media trends or consumption patterns may yield different results in the future. Contributions: This study extends dynamic capability theory by demonstrating that digital interactions generate new capabilities when organizations use social media to identify consumer needs, make informed decisions, and refine strategies.